2016
DOI: 10.1371/journal.pone.0147784
|View full text |Cite
|
Sign up to set email alerts
|

Fat King Penguins Are Less Steady on Their Feet

Abstract: Returning to the shore after a feeding sojourn at sea, king penguins often undertake a relatively long terrestrial journey to the breeding colony carrying a heavy, mostly frontal, accumulation of fat along with food in the stomach for chick-provisioning. There they must survive a fasting period of up to a month in duration, during which their complete reliance on endogenous energy stores results in a dramatic loss in body mass. Our aim was to determine if the king penguin’s walking gait changes with variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Modern penguins use their cornified feet and tarsometatarsi for much more than walking or resting, including propelling themselves in prone positions on land or ice, gripping and holding onto icy surfaces, and are also very important in underwater flight, assisting with steering the bird as it swims Stonehouse, 1967;Bedford, 1970;Hui, 1985;Parfitt and Vincent, 2005). It has also been observed that the presence, shape, and position of feet in extant penguins during underwater flight reduced drag and completed a more hydrodynamic shape (Parfitt and Vincent, 2005), and may potentially facilitate heat retention when feet are placed in line with the body (Willener et al, 2016). Effectively, the evolution of the distinctive shortened tarsometatarsi in some of the earliest penguins may have evolved as an adaptation that augmented swimming capabilities (Willener et al, 2016).…”
Section: Palaeobiological Interpretations For Paleocene Chatham Islanmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern penguins use their cornified feet and tarsometatarsi for much more than walking or resting, including propelling themselves in prone positions on land or ice, gripping and holding onto icy surfaces, and are also very important in underwater flight, assisting with steering the bird as it swims Stonehouse, 1967;Bedford, 1970;Hui, 1985;Parfitt and Vincent, 2005). It has also been observed that the presence, shape, and position of feet in extant penguins during underwater flight reduced drag and completed a more hydrodynamic shape (Parfitt and Vincent, 2005), and may potentially facilitate heat retention when feet are placed in line with the body (Willener et al, 2016). Effectively, the evolution of the distinctive shortened tarsometatarsi in some of the earliest penguins may have evolved as an adaptation that augmented swimming capabilities (Willener et al, 2016).…”
Section: Palaeobiological Interpretations For Paleocene Chatham Islanmentioning
confidence: 99%
“…It has also been observed that the presence, shape, and position of feet in extant penguins during underwater flight reduced drag and completed a more hydrodynamic shape (Parfitt and Vincent, 2005), and may potentially facilitate heat retention when feet are placed in line with the body (Willener et al, 2016). Effectively, the evolution of the distinctive shortened tarsometatarsi in some of the earliest penguins may have evolved as an adaptation that augmented swimming capabilities (Willener et al, 2016). While this likely led to greater reproductive success (Willener et al, 2016), a consequence of such shortened-hind limbs may have meant Kupoupou stilwelli n. gen. et sp., ?Crossvallia waiparensis and the Waipara Greensand giant were prone to high metabolic costs while walking, but also large lateral displacement of their feet, characteristic of an energetically conservative waddling gait observed in modern forms (Pinshow et al, 1977;Gauthier-Clerc et al, 2000), compared to the relatively less phylogenetically derived Waimanu manneringi and Muriwaimanu tuatahi.…”
Section: Palaeobiological Interpretations For Paleocene Chatham Islanmentioning
confidence: 99%
“…The lateral control of balance is particularly important in bipedal locomotion, e.g. in walking ducks [6], penguins [7], non-human primates [8] and humans [9,10], where the moving animal is only supported by a single limb for most of the walking cycle. During phases of single-limb support, the body may be modelled as an inverted pendulum [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although all of these sensors have previously been integrated into GPS tags with an increasing number of methods available for identifying behavioural states using such sensors, these analyses rely heavily on (a) movement data and precise location estimates to infer behaviour from turning angles (e.g. Garriga et al, 2016; Munden et al, 2019; Potts et al, 2018; Seidel et al, 2018; Williams et al, 2020), (b) multi‐second tri‐axial acceleration and bearing (Bidder et al, 2015; Hernández‐Pliego et al, 2017; Willener et al, 2016; Williams et al, 2017) and/or (c) validation datasets for supervised machine learning (Leos‐Barajas et al, 2017; Resheff et al, 2014). PAM loggers, however, (a) cannot provide spatial information to infer turning angles.…”
Section: Introductionmentioning
confidence: 99%